Exile on Main Street – Towards A Counter-Existential Therapy (Existential Analysis: Journal of the Society for Existential Analysis, 2017)
Brexit saw the rise of nationalism, an idea founded on tribal violence against the other. But for Nietzsche the 'good European' transcends parochialism, whilst Said saw modern western culture as the work of exiles. Existentialism embraced the modern ontological condition of exile, endeavouring to describe existence in the absence of a subject whose nature is groundless. It promised to confront the philosophical tradition and its false hopes in order to account for displacement, absence, otherness, openness to radical ethics and socio-political transformation. Does the philosophy of existence (and existential psychotherapy) still answer for the above? Or do we need to formulate a counter-existential perspective?
Keywords: Exile; otherness; existential psychotherapy; logocentrism; differentialism.